Analysis of tebuconazole residues in coconut water, kernel and leaves using LC–MS/MS. (15th October 2021) - Suganthi, A.; Rajeswari, E.; Sivakumar, V.; Bhuvaneswari, K.; Madhu Sudhanan, E.; Sathiah, N.; Prabakaran, K.
Graphical abstract: Highlights: Development of QuEChERS method for detecting tebuconazole residue in coconut. Method sensitivity and accuracy obtained with all the three coconut matrix. Chromatography done with LC and qualitative identification by TQD. Detection of residues in leaf, water and kernel after rooting feeding in coconut. Abstract: A method was validated for determining tebuconazole residues in coconut water, kernel and leaves using Liquid chromatography-Mass spectrometry/Mass spectrometry (LC–MS/MS) with electro spray ionization in positive ion mode. Samples were extracted with acetonitrile and subsequent clean-up was done using dispersive solid phase extraction. Recovery ranged between 70 and 114.39 % and the RSD was between 0.64 and 10.24 %. Root feeding studies with tebuconazole @ 5 and 10 mL/100 mL of water/tree revealed the presence of tebuconazole residues in coconut leaves until three days after treatment but dissipated to below quantifiable limit on 5th day at single dose while the residues went below quantifiable limit after 10 days at double the dose. Residues were below quantifiable limit in coconut water and kernel until three days. Data obtained from the study were used for estimating the risks associated with the exposures to tebuconazole residues in coconut.